Lesson Learned from Killer Floods in Kerala: Time for Retrospection - Raveesh Agarwal (Management and Economics Research Journal, 2018)
We know that the climate of the earth has undergone drastic change over periods of time. Natural factors and anthro- pogenic factors both contributed to climate change. Kerala is one of the most famous tourist destinations in India. The state saw one of its worst monsoon disasters in August 2018. There is huge loss and displacement of more than a million of people due to unusually high and persistent monsoon rains in Kerala. The objectives of this paper are to find out the reasons of disaster in Kerala and lessons learned from it. Some people believe that Kerala’s disaster is man made, while others say that it is a natural calamity. Whatever it may be, we have to identify the reasons for the same. Due to climate change and natural disasters, the impact on water, air, agriculture, infrastructure, health, education, bio-diversity, for- ests, and socioeconomic sectors is bound to increase. Nobody can stop the natural disasters, but we can take certain steps to lower the intensity. It is very much important to understand the lessons so that the effect of such type of events is minimized.